2018
DOI: 10.1176/appi.ps.201600422
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Caregivers of Individuals With a Diagnosis of Schizophrenia or Schizoaffective Disorder

Abstract: Caregiver distress was relatively high and related to multiple variables, some of which are potentially modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
3
28
1
1
Order By: Relevance
“…These findings may be related to a better adherence to medication associated with LAI use compared with oral antipsychotics [15][16][17] . Better adherence may relieve parental concerns over discontinuation of medication use by their offspring and reduce the need for monitoring of medication taking behaviour 29 . Our previous study showed that parents of patients with schizophrenia in general have a higher risk of psychiatric health care use compared with parents of patients with MS, rheumatoid arthritis, epilepsy or healthy controls 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may be related to a better adherence to medication associated with LAI use compared with oral antipsychotics [15][16][17] . Better adherence may relieve parental concerns over discontinuation of medication use by their offspring and reduce the need for monitoring of medication taking behaviour 29 . Our previous study showed that parents of patients with schizophrenia in general have a higher risk of psychiatric health care use compared with parents of patients with MS, rheumatoid arthritis, epilepsy or healthy controls 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Subjective family burden of schizophrenia is higher when the patient has lower levels of functioning 21,24 , apparent psychotic symptoms or abnormal behaviour [25][26][27] , negative symptoms 28 , and when providing frequent caregiving assistance, monitoring medication and having limited social support 29 . In addition, risk of medication discontinuation and concerns about medication effectiveness are two significant indicators of caregivers' distress 29 . Poor adherence to antipsychotic treatment has been associated with caregiver burden and experience of anxiety by family caregivers 30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scree plot showed that the slope started to change and drop dramatically after the third factor. Thus factor analysis was repeated by Direct Oblimin with three factors and the items with factor value less than 0.45 (item numbers 1, 3,11,12,19) were removed. Thereby, the scale had 3 factors and 14 items.…”
Section: Construct Validitymentioning
confidence: 99%
“…On the one hand, family members feel responsible for their relatives' illnesses, on the other hand, they exposed to negativistic attitudes from their environment and start to blame themselves. Difficulties of being a relative of a patient with schizophrenia and the psychosocial troubles are revealed through qualitative and quantitative studies [15][16][17][18][19]. In fact, some family members feel as if they have committed a disgraceful act and steer away from their social environments.…”
Section: Introductionmentioning
confidence: 99%